KUALITAS PELAYANAN DISTRIBUSI BERAS BERSUBSIDI PERUM BULOG DIVISI REGIONAL SUMATERA SELATAN PADA KELURAHAN 35 ILIR KECAMATAN ILIR BARAT II PALEMBANG - DERI DARFIN (Program Studi Magister Manajemen FE Unsri, 2014)
This study entitled the quality of subsidized rice distribution service of Bulog Coorporation of South Sumatera Regional Division in the Village of 35 Ilir. Formulation of the problem in this study is how the quality of subsidized rice distribution service Palembang Municipality work unit to the distributor of Sub District of West Ilir II, subsidized rice distribution service of Sub District of West Ilir II to the distributor of 35 Ilir Village, and subsidized rice distribution service of 35 Ilir Village to the rice subsidized beneficiary of RTS-PM. The method use in this study is a descriptive study with a qualitative approach. Assessment of subsidized rice distribution service quality is determined by five dimensions on three distribution services. The results of the data analysis showed that the quality of subsidized rice distribution services on the three services has met indicators on five dimensions, only in the subsidized rice distribution service there is no means for receiving complaints and suggestions and the lack of access to information that can be reached. There is a delay for subsidized rice distribution services in the Village of 35 Ilir to the RTS-PM beneficiary because it depends on the freight cars and deposited cost. Focus on attention of the equipment improvement and official physic facilities in the service of subsidized rice distribution